Transcriptome Analysis of Banana (Musa acuminate L.) in Response to Low-Potassium Stress - Min Xu; Can-Bin Zeng; Rui He; Zhen Yan; Zhao Qi; Rui Xiong; Yu Cheng; Shuang-Shuang Wei; Hua Tang (Agronomy, 2019)
Potassium (K+) is an abundant and important macronutrient for plants. It plays crucial roles in many growth and developmental processes, and growth is inhibited under low −K+ conditions. The molecular mechanisms operating under K+ starvation have been little reported in banana, which is a non-model plant. We conducted a transcriptome analysis of banana (Musa acuminata L. AAA group, cv. Cavendish) in response to low −K+ stress. The phenotypic traits and transcriptomic profiles of banana leaves and roots were compared between low −K+ (LK) and normal −K+ (NK) groups. The phenotypic parameters for the LK group, including fresh and dry weight, were lower than those for the NK group, which suggested that low −K+ stress may inhibit some important metabolic and biosynthetic processes. K+ content and biomass were both decreased in the LK group compared to the NK group. Following ribonucleic acid sequencing (RNA-Seq), a total of 26,796 expressed genes were detected in normal −K+ leaves (NKL), 27,014 were detected in low −K+ leaves (LKL), 29,158 were detected in normal −K+ roots (NKR), and 28,748 were detected in low −K+ roots (LKR). There were 797 up-regulated differentially expressed genes (DEGs) and 386 down-regulated DEGs in NKL versus LKL, while there were 1917 up-regulated DEGs and 2830 down-regulated DEGs in NKR versus LKR. This suggested that the roots were more sensitive to low −K+ stress than the leaves. DEGs related to K+ transport and uptake were analyzed in detail. Gene functional classification showed that the expression of genes regarding ABC transporters, protein kinases, transcription factors, and ion transporters were also detected, and may play important roles during K+ deficiency.